2020
DOI: 10.1371/journal.pone.0227626
|View full text |Cite|
|
Sign up to set email alerts
|

Preliminary evaluation of a novel nine-biomarker profile for the prediction of autism spectrum disorder

Abstract: BackgroundAutism spectrum disorder (ASD) is a complex group of heterogeneous neurodevelopmental disorders the prevalence of which has been in the rise in the past decade. In an attempt to better target the basic causes of ASD for diagnosis and treatment, efforts to identify reliable biomarkers related to the body's metabolism are increasing. Despite an increase in identifying biomarkers in ASD, there are none so far with enough evidence to be used in routine clinical examination, unless medical illness is susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 45 publications
3
25
0
1
Order By: Relevance
“…However, the diagnostic methods and screening tools utilized for ASD are somewhat subjective and are difficult to assess in younger children. Early diagnosis is critical because not only are intensive behavioral therapy programs effective in decreasing maladaptive behaviors in many children with ASD [ 8 ], the benefits of early intervention are typically greater the earlier the intervention begins [ 9 , 10 ]. A biological marker that could predict ASD risk, assist in early diagnosis, or even identify potential therapeutic targets has great clinical utility [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the diagnostic methods and screening tools utilized for ASD are somewhat subjective and are difficult to assess in younger children. Early diagnosis is critical because not only are intensive behavioral therapy programs effective in decreasing maladaptive behaviors in many children with ASD [ 8 ], the benefits of early intervention are typically greater the earlier the intervention begins [ 9 , 10 ]. A biological marker that could predict ASD risk, assist in early diagnosis, or even identify potential therapeutic targets has great clinical utility [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on our current understanding of the etiology of ASD, many blood-based biomarker candidates have been investigated [ 13 ], particularly neurotransmitters [ 14 ], cytokines [ 15 ], markers of mitochondrial dysfunction [ 10 , 16 ], and markers of oxidative stress and impaired methylation [ 17 , 18 ]. We have previously demonstrated that thyroid-stimulating hormone (TSH) and interleukin-8 (IL-8) were effective for separating boys with ASD from healthy control subjects, and levels were correlated with the severity of ASD [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abruzzo et al 48 highlighted the advantage of using ROC curves as an outstanding statistical tool for the identification of biomarkers that are sufficiently sensitive and specific for the early diagnosis of obesity. Although its utility in prediction, risk valuation, and assessment of therapeutic interventions still requires further validation, ROC curves emphasize the most significant statistical differences between patients and controls and even animal models of diseases 49 . The AUC provides a useful measure to evaluate the predictive value of biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…The pineal gland is responsible for the synthesis of serotonin and N-N-dimethyltryptamine during the day and melatonin synthesis at night, with the circadian rhythm [ 10 ]. Although melatonin is known for its regulatory role in the circadian rhythm, it is also a powerful antioxidant, it has anti-inflammatory properties, and it helps regulate immune response and synaptic plasticity [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%